Rapid iodine capture from radioactive wastewater by green and low-cost biomass waste derived porous silicon–carbon composite. Issue 9 (27th January 2021) - Qu, Guiyang; Han, Ying; Qi, Junjun; Xing, Xinyue; Hou, Minjie; Sun, Yang; Wang, Xing; Sun, Guangwei
Abstract : The effective and safe capture and storage of radioactive iodine ( 129 I or 131 I) are of significant importance during nuclear waste storage and nuclear energy generation. Abstract : The effective and safe capture and storage of radioactive iodine ( 129 I or 131 I) are of significant importance during nuclear waste storage and nuclear energy generation. Herein, a porous silicon–carbon (pSi–C) composite derived from paper mill sludge (PMS) is synthesized and used for rapid iodine capture. The influences of the activator type, the impregnation ratio of the paper mill sludge to the activator, carbonization temperature, and carbonization time on the properties of the pSi–C composite are investigated. The pSi–C composite produced in the presence of ZnCl2 as the activator and at an impregnation ratio of 1 : 1, a carbonization temperature of 550 °C, and a carbonization time of 90 min has a surface area of 762.13 m 2 g −1 . The as-synthesized pSi–C composite exhibits promising iodine capture performance in terms of superior iodine adsorption capacity ( q t ) of around 250 mg g −1 and rapid equilibrium adsorption with in 15 min. The devised method is environmentally friendly and inexpensive and can easily be employed for the large-scale production of porous silicon-activated carbon composites with excellent iodine capture and storage from iodine-contaminated water.